(untitled) (Annals of Medical Research, 2023)
Aim: Despite advances in the treatment of cardiovascular diseases, coronary artery disease (CAD) is the leading cause of death worldwide. The media layer of normal and diseased arteries contains lipoprotein-associated phospholipase A2 (Lp-PLA2), which is mostly made by mast cells, T lymphocytes, and monocytes. Our research aimed to define how the Lp-PLA2 and V279F gene polymorphisms are related to CAD. Materials and Methods: This study included 109 CAD patients and 71 controls. Fasting blood glucose (FBG) and lipid profiles were measured via the enzymatic colorimetric technique. Lp-PLA2 levels were detected with ELISA. The genomic DNAs were isolated from whole blood. Real-time polymerase chain reaction (RT-PCR) with the V279F mutation detection kit was used to identify the Lp-PLA2 V279F mutation. Results: In the CAD group compared to controls, serum Lp-PLA2 levels were higher (p 0.001). While FF (mutant) genotypes and VF (heterozygous) genotypes were absent in both groups, the Lp-PLA2 V279F mutation was discovered as the VV (wild) genotype in both the CAD group and controls. Conclusion: As a result, we determined that the Lp-PLA2 V279F mutation cannot be considered a genetic risk factor for CAD, but that Lp-PLA2 elevation may be an important parameter for CAD.